1. The problem statement, all variables and given/known data Resolve the following equation: log2 x + log2 [(x-3)/5)] = 3 2. Relevant equations Logarithmic laws: logc m + logc n = logc mn 3. The attempt at a solution Restriction: (x-3)/5 > 0 x-3 > 0 x > 3 Resolution: log2 x + log2 [(x-3)/5)] = 3 log2 x[(x-3)/5)] = 3 log2 [(x2 - 3x)/5x] = 3 23 = (x2 - 3x)/5x 8 = (x2 - 3x)/5x 8(5x) = x2 - 3x 40x = x2 - 3x 40x + 3x = x2 43x = x2 43 = x2 / x 43 = x My answer book says the answer is 8 however I don't seem to get to that after numerous attempts. Thank you in advanced.